The novel mesityloxy substituted metallo-phthalocyanine dyes with long fluorescence lifetimes and high singlet oxygen quantum yields - ALTUN, SELÇUK; ODABAŞ, ZAFER (ELSEVIER SCIENCE SA, 2016)
The synthesis of novel peripheral or non-peripheral tetra-mesityloxy substituted metal-free, zinc and indium phthalocyanines, which are highly soluble in organic solvents, has been achieved. The phthalocyanines have been characterized by UV-vis, IR, MALDI-TOF Mass, H-1 NMR, C-13 NMR spectroscopies and elemental analysis. On their spectroscopic, photochemical and photophysical properties, the effects of the substituent position and the variety of central metal ions in phthalocyanine cavity are also investigated. Photodegradation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes in dimethylformamide for the phthalocyanines are described. These properties of the compounds are very useful for photodynamic therapy applications and their high singlet oxygen quantum yields are very important for Type II mechanisms. The phthalocyanines can be appropriate candidates as Type II photosensitizers. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Trimethylphenoxy; Phthalocyanine; Mesityloxy; Photophysical; Photochemical; Photosensitizers; BEARING ZINC PHTHALOCYANINES; SENSITIZED SOLAR-CELLS; PHOTOCHEMICAL PROPERTIES; INDIUM(III) PHTHALOCYANINES; SILICON PHTHALOCYANINES; ELECTRONIC ABSORPTION; PHOTODYNAMIC THERAPY; HUMAN-DISEASE; PHOTOSENSITIZERS; PHOTOPHYSICS